2012
DOI: 10.1134/s1068162012020161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single-stranded DNA binding proteins on template/primer-independent DNA synthesis in the presence of nicking endonuclease Nt.BspD6I

Abstract: In the presence of the Nt.BspD6I nicking endonuclease DNA polymerase Bst stimulates intensive template/primer-independent DNA synthesis. Template/primer-independent DNA synthesis could be the reason for appearing nonspecific DNA products in many DNA amplification reactions particularly in the reactions with using nicking endonucleases. Search of the modes for inhibition template/primer-independent DNA synthesis becomes an urgent task because of broadening the DNA amplification methods with using nicking endonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This kind of non-specic reaction has not been well understood and lacks efficient suppressing methods, resulting in a major impediment to the practical applications of the NE-SDA methods. 13 A recent report found that the single-stranded DNA binding protein T4 bacteriophage gene 32 (T4gp32) could inhibit the RE-pol DNA synthesis; 37 our observation proved that AuNPs might also be inhibitors to this poorly-understood non-specic reaction. Also, thanks to the sensitive response of the surface plasmon of AuNPs to the environment, the interaction between AuNPs and the reaction components was monitored by UV-Vis spectroscopy, which aided in further understanding the way AuNPs inuence the amplication reactions and in tuning the concentration of AuNPs.…”
supporting
confidence: 58%
“…This kind of non-specic reaction has not been well understood and lacks efficient suppressing methods, resulting in a major impediment to the practical applications of the NE-SDA methods. 13 A recent report found that the single-stranded DNA binding protein T4 bacteriophage gene 32 (T4gp32) could inhibit the RE-pol DNA synthesis; 37 our observation proved that AuNPs might also be inhibitors to this poorly-understood non-specic reaction. Also, thanks to the sensitive response of the surface plasmon of AuNPs to the environment, the interaction between AuNPs and the reaction components was monitored by UV-Vis spectroscopy, which aided in further understanding the way AuNPs inuence the amplication reactions and in tuning the concentration of AuNPs.…”
supporting
confidence: 58%
“…This preference may be manifested by palindromic sequences, as well as a number of other peculiarities. Thus, an increased temperature significantly increased GC content of synthesized DNAs (Ogata & Miura, ); the addition of SSB proteins affected the efficiency of the synthesis (Zyrina et al ., ), whereas the presence of REases resulted in the appearance of their recognition sites in the reaction products (Liang et al ., ). However, relative distribution of these sites and their orientation as well as the context and the size of spacer regions are poorly predictable.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is significant in studies of the possibilities for the direct creation of genetic information by a protein and for an understanding of possible mechanisms of genome evolution. The ab initio DNA synthesis is considered one of the causes of the appearance of nonspecific products in isothermal DNA amplification reactions (Inoue et al ., ; Tan et al ., ; Zyrina et al ., ; He & Jiang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a new strategy was offered for isothermal DNA amplification in the presence of nicking enzymes (Zyrina et al, 2012). It was based on the use of SSB proteins as inhibitors of non-specific ab initio synthesis.…”
Section: Discussionmentioning
confidence: 99%